2015
DOI: 10.3402/ljm.v10.26771
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenvitamin D receptor genepolymorphisms and chronic periodontitis among Libyans

Abstract: BackgroundChronic periodontitis (CP) is a common oral disease characterized by inflammation in the supporting tissue of the teeth ‘the periodontium’, periodontal attachment loss, and alveolar bone loss. The disease has a microbial etiology; however, recent findings suggest that the genetic factors, such as vitamin D receptor (VDR) gene polymorphisms, have also been included.AimInvestigation of the relationship between VDR gene polymorphisms and CP among Libyans.Materials and methodsIn this study, we examined 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
3
13
0
3
Order By: Relevance
“…El Jilani et al reported that there was no significant association between CP and FokI A/G SNP rs2228570 in a Libyan population which was in accordance with our present study. A study performed by Arroyave et al in a Colombian population showed that although the rs2228570 ( FokI ) polymorphism remains a potentially functional variant, there was no association either between the different genotype/allele frequencies or haplotype and CP; it does not appear to be in linkage disequilibrium with the BsmI , ApaI or TaqI polymorphic sites, which was in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…El Jilani et al reported that there was no significant association between CP and FokI A/G SNP rs2228570 in a Libyan population which was in accordance with our present study. A study performed by Arroyave et al in a Colombian population showed that although the rs2228570 ( FokI ) polymorphism remains a potentially functional variant, there was no association either between the different genotype/allele frequencies or haplotype and CP; it does not appear to be in linkage disequilibrium with the BsmI , ApaI or TaqI polymorphic sites, which was in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a Chinese study of 51 patients with generalized AgP and 53 healthy controls concluded that the FF‐VDR (OR = 2.90) and the F allele (OR = 2.02) might increase susceptibility of AgP 20 . In another study, 99 patients with CP and 97 healthy controls in Libya were investigated, and no association between rs2228570 and CP was detected 21 . Recently, FF and Ff genotypes were associated with increased susceptibility to severe CP in 1,460 Thai patients 22 .…”
mentioning
confidence: 96%
“…To date, only a few studies 18–22 have focused on the relationship between rs2228570 and periodontitis. In 2003, 74 patients with chronic periodontitis (CP) and 94 healthy controls were studied, but no association between rs2228570 and CP was observed 18 .…”
mentioning
confidence: 99%
“…12 In a Libyan study of 99 CP patients and 97 controls, the lack of association between rs2228570 and CP was reported again. 13 On the contrary, in a Thai study with a large sample size of 1460 participants, both FF and Ff genotypes were reported to be more susceptible to severe CP. 14 Recently, it was revealed by a Romanian study including 53 CP patients and 47 controls that both FF and Ff genotypes were more likely to develop CP than ff genotype, 15 which is in line with the results of the Thai study.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, in a Chinese study of 107 severe CP patients and 121 controls, no association between rs2228570 and severe CP was reported . In a Libyan study of 99 CP patients and 97 controls, the lack of association between rs2228570 and CP was reported again . On the contrary, in a Thai study with a large sample size of 1460 participants, both FF and Ff genotypes were reported to be more susceptible to severe CP .…”
Section: Introductionmentioning
confidence: 95%